Pregnenolone Inhibits Doxorubicin-Induced Cardiac Oxidative Stress, Inflammation, and Apoptosis-Role of Matrix Metalloproteinase 2 and NADPH Oxidase 1 - Mohamed A. Morsy; Seham A. Abdel-Gaber; Sahar A. Mokhemer; Mahmoud Kandeel; Wael F. Sedik; Anroop B. Nair; Katharigatta N. Venugopala; Hany Ezzat Khalil; Bandar E. Al-Dhubiab; Mervat Z. Mohamed (MDPI AG, 2023)
The clinical usefulness of doxorubicin (DOX) is limited by its serious adverse effects, such as cardiotoxicity. Pregnenolone demonstrated both anti-inflammatory and antioxidant activity in animal models. The current study aimed to investigate the cardioprotective potential of pregnenolone against DOX-induced cardiotoxicity. After acclimatization, male Wistar rats were randomly grouped into four groups: control (vehicle-treated), pregnenolone (35 mg/kg/d, p.o.), DOX (15 mg/kg, i.p, once), and pregnenolone + DOX. All treatments continued for seven consecutive days except DOX, which was administered once on day 5. The heart and serum samples were harvested one day after the last treatment for further assays. Pregnenolone ameliorated the DOX-induced increase in markers of cardiotoxicity, namely, histopathological changes and elevated serum levels of creatine kinase-MB and lactate dehydrogenase. Moreover, pregnenolone prevented DOX-induced oxidative changes (significantly lowered cardiac malondialdehyde, total nitrite/nitrate, and NADPH oxidase 1, and elevated reduced glutathione), tissue remodeling (significantly decreased matrix metalloproteinase 2), inflammation (significantly decreased tumor necrosis factor-α and interleukin 6), and proapoptotic changes (significantly lowered cleaved caspase-3). In conclusion, these findings show the cardioprotective effects of pregnenolone in DOX-treated rats. The cardioprotection achieved by pregnenolone treatment can be attributed to its antioxidant, anti-inflammatory, and antiapoptotic actions.